Inhibitory effect of edaravone on systemic inflammation and local damage in skeletal muscles following long-term ischemia to murine hind limb. (23rd September 2019) - Yokoyama, Hirokazu; Tsujii, Masaya; Iino, Takahiro; Nakamura, Tomoki; Sudo, Akihiro
Purpose: The purpose of this study was to evaluate local and systemic pathology in a murine model of ischemia–reperfusion (I/R) injury induced by long-term application of a tourniquet on the hind limbs and to assess the protective effects of edaravone, a potent systemic scavenger of free radicals, using this model. Methods: Sixty C57BL6 mice were divided in two groups, with one group receiving a 3 mg/kg intraperitoneal injection of edaravone and the other group receiving an identical amount of saline 30 min before ischemia under deep anesthesia. The left thigh of each animal was constricted for 4 h with a 4.5-oz. orthodontic rubber band to induce ischemia; 4 h was the critical duration for skeletal muscles. After ischemia, specimens of skeletal muscles, both kidneys, and plasma were collected at 0, 2, 12, 24, 48, and 72 h. Injury to the skeletal muscles and vacuolar degeneration of the kidneys were histologically assessed. Additionally, apoptosis of skeletal muscle cells was assessed by analysis of caspase 3/7 activity and TUNEL staining. Plasma tumor necrosis factor (TNF)-α levels were measured using an enzyme-linked immunosorbent assay kit. Results: Skeletal muscles exhibited prominent injury of myofibers at 12 h after I/R injury, with clear upregulation of plasma TNF-α expression and histologic evidence of tubular dysfunction of the kidneys. Plasma TNF-α levels declined and histologic renal damage was ameliorated in edaravone-treated mice, but treatment did not protect skeletal muscle following ischemia for 4 h. Nonetheless, compared with group S, expression of the apoptosis marker caspase 3/7 was significantly inhibited in the skeletal hind limb muscles of Ed-group mice affected by reperfusion injury following ischemia for 4 h. Conclusion: The present study demonstrated that edaravone is a potentially useful drug for systemic or local treatment of reperfusion injury resulting from long-term ischemia.